The Role of Speech-Language Pathology in an Interdisciplinary Care Model for Persistent Symptomatology of Mild Traumatic Brain Injury - Hardin, Kathryn Y.; Kelly, James P. (Seminars in Speech and Language, 2019)
The Marcus Institute for Brain Health (MIBH) provides interdisciplinary care for adults struggling with persistent effects of mild traumatic brain injury and accompanying changes in behavioral health, with specific emphases on Veterans and retired elite athletes. The cognitive, physical, and behavioral symptoms associated with mild traumatic brain injury are interrelated, with neurobiopsychosocial modeling encompassing the factors related to recovery from a traumatic brain injury. The diffuse impacts of chronic concussive injuries require multiple clinical providers to address the breadth of symptoms, facilitating both interdisciplinary and transdisciplinary care models. By implementing integrated practice units, patients receive advanced medical care, imaging, speech-language pathology, physical therapy, behavioral health, neuropsychology, and clinical pharmacy for a cohesive diagnostic and intervention plan. Nationally, speech-language pathologists report challenges with best-practice options for concussion, particularly in the domain of assessment practices. At the MIBH, speech-language pathologists begin their assessment with a structured clinical interview that focuses on patients' needs and concerns. Evaluation modalities focus on hearing, communication, and functional cognition to guide therapeutic treatment planning. The intensive outpatient care program at MIBH incorporates both individual sessions targeting patient-centered goals and group care, where speech-language pathologists work transdisciplinarily to generalize care from all disciplines out into the community. Care practices for concussive injuries continue to evolve rapidly; speech-language pathology at the MIBH offers one such vision for excellence in clinical care.
Keywords: speech pathology; speech therapy; concussion; mild traumatic brain injury; interdisciplinary